A Moral Extension Of The Theory Of Planned Behavior To Predict Consumers’ Purchase Intention For Energy-Efficient Household Appliances - Tan, Chin Seang (2014)
The electricity consumption throughout the world has been in the rapid rise over the past decades and the global primary energy demand is expected to rise by around one-third from now to 2035. However, the current investment trend it is indeed showing warning signs of power supply inadequacy. In view of the imbalance situation, many countries are increasingly aware of the urgency and importance of wiser and better use of energy resources and have embraced energy efficiency as a partial solution to looming energy problems. In reality, many people are still not replacing their household appliances to the energy-efficient ones.